Solusi Konflik Peran Perempuan Minangkabau (Kasus Perawat yang Melanjutkan Pendidikan ke Perguruan Tinggi) - Nola Mutiara Asril; Maihasni Maihasni; Alfitri Alfitri (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
This article is about nurses who continue their education to universities it required by law no. 38 of 2014 of Nursing to continue to level SI (university graduate). According to by law declared a nursing graduate Sekolah Perawat Kesehatan (SPK) who did not continue their study, will be a nursing assistant or administrative personnel. However, they do not get the task of study and only get the permission of studying and this keeps them working when they have to follow the SI education program. As a mother, worker, and student, nurses have three roles, the busy of these three roles need to be bridged to align themselves as a social being that connected to the community environment. The research question is what is the solution undertaken by students who work as nurses to save the role of the community? This article will show that Minang women who continue their education and work as nurses trying to save their role in their community at the time they are busy.